Speed detection of moving vehicle using normal camera - Nur Adila , Mamat (2012)
It was recorded that road vehicle accidents in Malaysia were increasing year by year. One of the main factors that caused road accident is due to over limit speed of vehicle. Road transportation department and polices have been enforced the speed limits of vehicle to control the road accidents. Normal practice of polices is to put the speed gun at the spotted areas to detect a vehicle drives over the speed limit. However, due to lack number of speed guns available, only a few target roads can be monitored by policemen and this will result in less of enforcement laws to the drivers that drive over the speed limit. In current technology of digital camera and digital images, the image analysis using normal camera to measure the speed of moving vehicle can be obtained. An algorithm of vehicle detection will be introduced to measure the speed of vehicle captured by normal camera. Image processing can serve the requirement of low cost of investment. Image processing is the technology, which is based on a software component that does not require a special hardware. With a typical video camera and normal computer, a speed detection device can be created. By using basic scientific velocity theory, the speed of moving vehicle in the video can be calculated from the known distance and time, which the vehicle has moved beyond.